Complexes of 2-Thioracil with Some Divalent Metal Ions - N. Singh, Bardi; P. Singh, Udai; Ghose, R.; K. Ghose, Animesh (Asian Journal of Chemistry, 2010)
Simple complexes of Mn(II), Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) with 2-thiouracil (TU) have been prepared and characterized by various physico-chemical methods. IR results show that 2-thiouracil is bidentate in all cases, coordinating through sulphur and one nitrogen atom. The X-ray powder pattern of the complexes suggests orthorhombic symmetry for Mn(II)-2TU, Co(II)-2TU, Mi(II)-2TU, Zn(II)-2TU and tetragonal symmetry for Cu(II)-2TU complexes.